KONSEP PENDIDIKAN ISLAM MENURUT PEMIKIRAN SUNAN KALIJAGA DALAM TEMBANG LIR-ILIR - Fuad Ahmad Riva’i; Mira Nurdianti (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2018)
The background of this research is to find out more deeply about the values ​​of Islamic education according to the thoughts of Sunan Kalijaga contained in the song Lir-ilir and to be used as guidelines for educational activities. This study uses qualitative research with the type of library research. So in data collection using primary data sources and secondary data. Primary data can be obtained in books that focus on Sunan Kalijaga. Meanwhile, secondary data is data taken from journals. After conducting studies, observations, research and analysis of several works of Sunan Kalijaga, the results of this research are: in the song Lir-ilir by Sunan Kalijaga there are values ​​of Islamic education, the objectives of Islamic education, the concept of educators in Islamic education, Islamic education materials, methods Islamic education, and the value of character education. From the results of this study it can be concluded that Islamic education is process-oriented. Emphasis on practical material in the implementation of the Islamic education process. Prioritizing moral values ​​and karma in an educational environment as an effort to maximize the achievement of the goals of Islamic education. Combining classical and modern intellectual treasures in planning, theory, and practice of Islamic education